Effects of N‐Acetylcysteine on the reproductive performance, oxidative stress and RNA sequencing of Nubian goats. Issue 1 (18th August 2020) - Luo, Jinhong; Ao, Zheng; Duan, Zhiqiang; Ao, Ye; Wei, Shinan; Chen, Wei; Chen, Xiang
Abstract: N‐acetylcysteine (NAC) has been found to enhance the protective ability of cells to counter balance oxidative stress and inflammation. To investigate the effects of dietary NAC supplementation on the reproductive performance of goats, the reproductive performance and endometrial transcriptome of goats fed with diets with NAC (NAC group) and without NAC supplementation (control group) were compared. Results showed that the goats fed with 0.03% and 0.05% NAC had similar litter size, birth weight, nitric oxide (NO), sex hormones and amino acids levels compared with the goats of the control group. However, feeding with 0.07% NAC supplementation from day 0 to day 30 of gestation remarkably increased the litter size of goats. The goats of the 0.07% NAC group presented increased levels of NO relative to the control group, but their sex hormones and amino acids showed no differences. Comparative transcriptome analysis identified 207 differentially expressed genes (DEGs) in the endometrium between the control and the 0.07% NAC groups. These DEGs included 146 upregulated genes and 61 downregulated genes in the 0.07% NAC group. They were primarily involved in the cellular response to toxic substances, oxidoreductase activity, immune receptor activity, signalling receptor binding, cytokine–cytokine receptor interactions, PI3K‐Akt signalling pathway and PPAR signalling pathway. In conclusion, results showed that dietary 0.07% NAC supplementation exerted a beneficial effect on the survival of goat embryos at the early pregnancy stage. Such positive outcome might be due to the increased NO production and affected expression of genes involved in the anti‐inflammation pathways of the endometrium. Abstract : Feeding with 0.07% NAC supplementation from day 0 to day 30 of gestation remarkably increased the litter size of Nubian ewes. Dietary 0.07% NAC supplementation exerted a beneficial effect on the survival of ewe embryos at the early pregnancy stage might be due to the increased NO production and affected expression of genes involved in the anti‐inflammation pathways of the endometrium.